2016
DOI: 10.18632/oncotarget.8323
|View full text |Cite
|
Sign up to set email alerts
|

Salivary HOTAIR and PVT1 as novel biomarkers for early pancreatic cancer

Abstract: Sensitive and non-invasive biomarkers for pancreatic cancer (PC) are lacking. We aimed to identify salivary long non-coding RNAs (lncRNAs) as biomarkers in diagnosis of resectable PC. Five well-documented lncRNAs: H19, HOTAIR, HOTTIP, MALAT1, PVT1, which are most closely associated with pancreatic cancer from previous studies were selected as putative lncRNA biomarkers. Their expression in pancreatic tissues and saliva of cancer patients and healthy controls was measured by quantification polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 18 publications
1
91
0
Order By: Relevance
“…One of the lncRNAs, HOX Transcript Antisense RNA (HOTAIR) has been shown to be strongly up-regulated in the saliva of pancreatic cancer patients (67). The H19, imprinted maternally expressed transcript (H19) is involved in promotion of pancreatic cancer metastasis CANCER GENOMICS & PROTEOMICS 14: 161-172 (2017) 168 The lead known protein-coding genes are shown.…”
Section: Discussionmentioning
confidence: 99%
“…One of the lncRNAs, HOX Transcript Antisense RNA (HOTAIR) has been shown to be strongly up-regulated in the saliva of pancreatic cancer patients (67). The H19, imprinted maternally expressed transcript (H19) is involved in promotion of pancreatic cancer metastasis CANCER GENOMICS & PROTEOMICS 14: 161-172 (2017) 168 The lead known protein-coding genes are shown.…”
Section: Discussionmentioning
confidence: 99%
“…When both salivary HOTAIR and PVT1 were combined for the diagnosis of PC, Xie et al found that their combination had good sensitivity and specificity. This result implies that salivary HOTAIR and PVT1 could be a novel non‐invasive and specific biomarker for the detection of PC.…”
Section: Pancreatic Cancer (Pc)mentioning
confidence: 99%
“…7 Among them, lncRNAs have acquired extensive attention, recently, as new regulators in many biological processes, such as transcriptional regulation, 8 differentiation, 9 immune response, 10 metabolism, 11 cell growth, and especially tumorigenesis. 12,13 Moreover, since an increasing number of reports have indicated that their abnormal expression is frequently observed in human cancers, some lncRNAs have been validated as biomarkers for diagnostic, metastasis, recurrence, and poor prognosis, [14][15][16][17] such as MALAT-1 for lung, glioma, gastric, and prostate cancer; [18][19][20][21] HOTAIR for breast, ovarian, pancreatic, and colorectal cancer; [22][23][24][25] and CCAT2 for oral squamous cell carcinoma and bladder cancer. 26,27 Zinc finger antisense 1 (ZFAS1) locus is host to three C/D-box small nucleolar RNAs (snoRNAs), and its transcription initiates from the antisense strand near the 5′ end of the protein-coding gene Znfx1.…”
Section: Introductionmentioning
confidence: 99%